THE OPERATION OF HEGEMONY IN VICTORIA AVEYARD’S RED QUEEN - Rachmawati, Ulul Azmi; Astutiningsih, Irana; Suwargono, Eko (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
Red Queen by Victoria Aveyard is dystopian, young adult fantasy novel setting up in the Kingdom of Norta where the construction of a class in society is determined by blood color; Silver and Red. In this novel, there is a depiction on how power and ruling position could be achieved by utilizing a process of negotiating beliefs and values rather than conducting a full coercive domination. The Silvers as the dominant class indoctrinating ideology using hegemonic apparatuses before finally gaining concensus and achieving ruling position from the Reds as subordinate class. This study uses qualitative research method. As the theoretical framework to analyze the data in the novel, this study utilizes the theory of hegemony by Antonio Gramsci. The purpose of this study is to discover how hegemony operation is constructed by the ruling class to subordinate class and to find out the ideological construction in Red Queen. The result of this study elaborates that hegemony operation works through several stages. This study also discover that hegemony operation depicted in the novel is correlatively related to the issue of racial discrimination and white supremacy in the United States. The ideological construction that is built in the Red Queen novel is to resist the totalitarian government with Silvers’ ideology that put the Reds powerless and inferior. From this result, it can be concluded that Red Queen as a cultural product acts as one of the hegemonic apparatuses to spread certain ideology of the author to the reader.